Hydrothermal reequilibration of igneous magnetite in altered granitic plutons and its implications for magnetite classification schemes: Insights from the Handan-Xingtai iron district, North China Craton. (15th September 2017) - Wen, Guang; Li, Jian-Wei; Hofstra, Albert H.; Koenig, Alan E.; Lowers, Heather A.; Adams, David
Abstract: Magnetite is a common mineral in igneous rocks and has been used as an important petrogenetic indicator as its compositions and textures reflect changing physiochemical parameters such as temperature, oxygen fugacity and melt compositions. In upper crustal settings, igneous rocks are often altered by hydrothermal fluids such that the original textures and compositions of igneous magnetite may be partly or completely obliterated, posing interpretive problems in petrological and geochemical studies. In this paper, we present textural and compositional data of magnetite from variably albitized granitoid rocks in the Handan-Xingtai district, North China Craton to characterize the hydrothermal reequilibration of igneous magnetite. Four types of magnetite have been identified in the samples studied: pristine igneous magnetite (type 1), reequilibrated porous magnetite (type 2), reequilibrated nonporous magnetite (type 3), and hydrothermal magnetite (type 4). Pristine igneous magnetite contains abundant well-developed ilmenite exsolution lamellae that are largely replaced by titanite during subsequent hydrothermal alteration. The titanite has a larger molar volume than its precursor ilmenite and thus causes micro-fractures in the host magnetite grains, facilitating dissolution and reprecipitation of magnetite. During sodic alteration, the igneous magnetite is extensively replaced by type 2 and type 3 magnetite via fluid-induced dissolution and reprecipitation. Porous type 2 magnetite is the initial replacement product of igneous magnetite and is subsequently replaced by the nonoporous type 3 variety as its surface area is reduced and compositional equilibrium with the altering fluid is achieved. Hydrothermal type 4 magnetite is generally euhedral and lacks exsolution lamellae and porosity, and is interpreted to precipitate directly from the ore-forming fluids. Hydrothermal reequilibration of igneous magnetite has led to progressive chemical purification, during which trace elements such as Ti, Al, Mg, Zn, and Cr contents decrease dramatically (up to 2–3 orders of magnitude different), coupled with significant increase in iron concentrations from less than 64 wt.% to higher than 70 wt.%. Results presented here show that magnetite is much more susceptible to textural and compositional reequilibration than previously thought. The reequilibrated magnetite has geochemical patterns that may be distinctively different from its precursor, making existing discrimination plots questionable when applied to genetic interpretation. Based on textural characterization and high-resolution in situ compositional analyses, we propose that the Fe versus V/Ti diagram can be more confidently used to discriminate between pristine igneous magnetite, reequilibrated magnetite, and hydrothermal magnetite.